Physical, Chemical and Biological Analysis of Water Environment Quality in Tourism Area as a Basis for Sustainable Ecotourism Development in Bogor - Aidha Zulaika; Tjahjo Tri Hartono; Hery Saputra; Endah Nadiya Stephanie (Jurnal Rekayasa Lingkungan dan Biosistem, 2025)
Lakes are an important part of the inland water system that functions to maintain environmental stability, support biodiversity, and provide ecosystem services such as clean water supply, flood control, and natural recreation space. This study was conducted to analyze the quality of the lake and the lake's carrying capacity for fisheries and tourism facilities. Physical, chemical, biological parameters, and lake fertility index were calculated referring to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 5 of 2021 concerning Procedures for Issuing Technical Approvals and Operational Feasibility Letters for Environmental Pollution Control. The results of the study found high pollution parameters in BOD, COD, and TDS. Lake Lido is classified as having a fairly high pollution load with a lake with a Eutrophic trophic index so that further analysis is needed for the level of pollution distribution, lake carrying capacity and lake utilization management strategies for sustainable fisheries and tourism activities. Recommended strategy of Domestic Wastewater Treatment Plant is a system which meet the quality standards for domestic wastewater based on Permen LHK No. 68 of 2016, with an integrated system. As environmentally friendly fish farming strategy that is recommended was the use of SMART Floating Net Cages (KJA).